PERANCANGAN ULANG VISUAL BRANDING ANTICLINE - NIDYA PUTRI, Drs. Syafwan, M.Si., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The Purpose of the redesign is to produce an Anticline visual brand. The new Anticline Visual Brand is expecte to be able to build and create a new awareness of the community so that it can increase the brand’s public awareness of this brand. The stage of Visual branding Redesigning begis wth collecting and continuing data analysis. The process of collecting data is done by obsevations, interviews, and documentation. Futhermore. Data analysis was carried out using the SWOT analysis method. Ending with the design stage.Anticline Visual branding Redesigning produces the main media in the form of Brandbook which contain a description of the brand, visual element and rules for implementing these element to the media so as to build viusal that are consistent with the Anticline brand characteristics. This design is also assisted by other media namely instagram, website, shopping bag, packaging, and stationery set.Keyword: Anticline, Visual branding, Brand, Brandbook.